Mind the Gap: Reconciling Formalism and Intuitionism in Computational Design Research - Zeynep Mennan (Footprint)
The paper discusses the epistemological and methodological implications of an increasing process of formalisation and naturalisation of knowledge within the context of the complexity paradigm. This process is argued to induce a shift in the nature of notations and representations, to which corresponds an epistemic shift from a graphic to a computational rationality, with substantial effects on current design methodologies and strategies used in computational design. The shortcomings of a heavy formalism are discussed with respect to a possible reconciliation between the operational efficiency of formalist representations and the recovery of the phenomenological grounds of design experimentations through a simultaneous articulation of formalist and intuitionist approaches in computational design research.